Thioredoxin regulates T cell proliferation and aggravates the severity of influenza a virus infection - Li Shen; Jing Yang; Jin Liu; Yue Zhang; Yue Wu; Hong Xu (Scientific Reports)
Abstract Different functional T lymphocytes play important roles in the progression of IAV infection, including proliferation, recruitment, and effector activity. However, the immune changes of T cells during IAV infection are unclear, and the related targets are still to be explored. In this study, we used a multi-omics approach combining transcriptome and single-cell transcriptome analysis to identify TXN as a key target gene and elucidate its close association with T-cell proliferation. From these data, we identified 10 key differential genes through a combination of differential analysis, WGCNA, and Friends analysis and further identified that only TXN and S100A6 co-existed in the highly variable genes of proliferative T cells. Because TXN exhibits highly specific high expression in proliferative T cells, we focused on its related research and ultimately identified it as a target gene for IAV infection. Reports have suggested that simultaneous inhibition of the GSH and TXN pathways can effectively trigger cell death. This proves our hypothesis about a new direction of T cell death in IAV infection. Additionally, we found that T cell development after IAV infection was regulated and altered, but this study did not clearly explain whether it was negative regulation. In summary, we have identified TXN as a target gene involved in T cell proliferation during IAV infection, and we suggest that its expression may be associated with non-apoptotic forms of T cell death.